ANALISIS MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KOMPENSASI SEBAGAI VARIABEL MEDIATOR - Untung Widodo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
Among the resources that supports the organization is human resources that have a central role. The central role of human resources is due to any shape and purpose made by various organizations for the benefit of human vision and mission execution is managed and taken care of humans, so if an organization wants to be able to achieve its goals by both the organization must be supported by human resources quality.The object of this research was conducted at the District Office employees Gunungpati. The population in this study were employees of the District Office Gunungpati and sampling using census techniques that produce samples totaling 68 employees. The data analysis technique used is the use of multiple linear regression analysis techniques.The results showed that there is a positive and significant influence of motivation variable (X) against compensation (Y1), there is a positive and significant effect of motivation variables (X2) on employee performance (Y2) and there is a positive and significant effect of  variable compensation (Y1) on employee performance (Y2).